2018
DOI: 10.1021/acsomega.8b01957
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of CO2 on Heterostructures of Bi2O3 Nanocluster-Modified TiO2 and the Role of Reduction in Promoting CO2 Activation

Abstract: The capture and conversion of CO 2 are of significant importance in enabling the production of sustainable fuels, contributing to alleviating greenhouse gas emissions. While there are a number of key steps required to convert CO 2 , the initial step of adsorption and activation by the catalyst is critical. Well-known metal oxides such as oxidized TiO 2 or CeO 2 are unable to promote this step. In addressing this difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 83 publications
(146 reference statements)
0
6
0
Order By: Relevance
“…The results showed that the properties of bismuth-containing oxides could be utilized to adsorb and excite carbon dioxide, which is the crucial first step in the reductive conversion of CO 2 to valuable molecules. This combination of Bi 3+ in TiO 2 species offers a fascinating composite that can stimulate CO 2 by strong adsorption and alteration or electron transfer to produce a carboxylate or by direct breaking of the C−O bond [76]. The use of metal oxides to load the noble elements in carbon dioxide conversion reactions was carried out using different oxides (TiO 2 , SiO 2 , γ-Al 2 O 3 , ZrO 2 , and CeO 2 ).…”
Section: Co 2 Conversion Using Catalyst-supporting Materialsmentioning
confidence: 99%
“…The results showed that the properties of bismuth-containing oxides could be utilized to adsorb and excite carbon dioxide, which is the crucial first step in the reductive conversion of CO 2 to valuable molecules. This combination of Bi 3+ in TiO 2 species offers a fascinating composite that can stimulate CO 2 by strong adsorption and alteration or electron transfer to produce a carboxylate or by direct breaking of the C−O bond [76]. The use of metal oxides to load the noble elements in carbon dioxide conversion reactions was carried out using different oxides (TiO 2 , SiO 2 , γ-Al 2 O 3 , ZrO 2 , and CeO 2 ).…”
Section: Co 2 Conversion Using Catalyst-supporting Materialsmentioning
confidence: 99%
“…The group converted CO 2 at an accelerated rate to CH 4 with 100 % selectivity. Nolan et al [61] investigated the CO 2 reduction response of Bi 2 O 3 -TiO 2 heterostructured photocatalysts and found out that the Bi 3 + rich oxide can be employed in the adsorption and excitation of CO 2 . As this activation process is the initial step in the CO 2 reduction and its conversion into useful chemical livestock, therefore this Bi 3 + rich TiO 2 system can enhance the CO 2 conversion attributed to the superior interaction and transfer of electrons to yield carboxylates or through CÀ O bond cleavage.…”
Section: Photocatalytic Co 2 Reductionmentioning
confidence: 99%
“…The formation of a transient negative ion by the injected electron is an important step in the CO 2 dissociation, and this can only be possible above the threshold voltage. TiO 2 modified with metal oxide nanoclusters possess enhanced activity to adsorb and convert CO 2 [26,140]. The Bi 2 O 3 -TiO 2 heterostructures obtained by modifying TiO 2 with Bi exhibited low coordinated Bi sites in the nanoclusters and a valence band edge consisting mainly of Bi-O states due to the presence of the Bi lone pair.…”
Section: Characteristic Adsorption Of Representative Metal Oxidesmentioning
confidence: 99%
“…The Bi 2 O 3 -TiO 2 heterostructures obtained by modifying TiO 2 with Bi exhibited low coordinated Bi sites in the nanoclusters and a valence band edge consisting mainly of Bi-O states due to the presence of the Bi lone pair. Upon interaction of CO 2 with the reduced heterostructures, CO or CO 2 − were observed mainly through electron transfer to CO 2 , and the Bi 2 O 3 -TiO 2 heterostructures became oxidized in the process with adsorbed CO 2 in carbonate form [140]. In a related study, clean or hydroxylated extended rutile and anatase TiO 2 surfaces modified with Cr nanoclusters presented an upshift valence band edge related to the existence of Cr 3d-O 2p interactions, which promoted the CO 2 activation.…”
Section: Characteristic Adsorption Of Representative Metal Oxidesmentioning
confidence: 99%